LINGKAR OLIGARKI PARTAI GOLKAR DI RIAU TAHUN 2003-2013 - MAYA WULAN SARI; HASANUDDIN " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Ring oligarchy RIAU year 2003-2013 Golkar Party. The research looked at how the existing oligarchy circumference at the Golkar party Riau , Riau where the government both at the executive and legislative branches in which there is a cadre of the Golkar party has always dominated the regional government of Riau . During Rusli Zainal served as governor of Riau in 2 periods , ie 1 of the 2003-2008 period , and a 2 -year period 2008-2013. Oligarchy is when being in front and behind the power that always overshadows the power of government . The person who plays this oligarchy is no friend of the environment , family , and even alumni. This description can also be referred to as a three-legged oligarchy , where the influence of the three will not be able to escape from the shadow of power , particularly the power of the local government of Riau . Political party , Golkar party is more specifically known as a party built on the new order , the journey and his work will always be overshadowed by three feet oligarchy .This study aims to look at how the role played by travel and oligarch and his people in control of government for the benefit of his people . This study used a qualitative approach in describing each phenomenon and analyzes encountered . This study uses as a resource person as an object informen information on this research . The use of informants as informen aims to strengthen the analysis will be concluded in answering the theory used . Data used in this study is primary data and secondary data obtained through the collection of data from a variety of media and direct interviews with sources of research . Analysis of the data in this study used a descriptive technique that aims to explain and describe the findings in the field .Based on the research that there is a three-legged oligarchy in Riau administration both in the executive and legislative branches , where they shared background of the Golkar party , during the second period of oligarchic leadership Rusli Zainal seen mainly in strategic positions held by his people . Strategic positions that would have paved the way oligarchs to achieve the goals they want , with the peak magnitude of the problem was the elucidation of PON fund corruption case related to the manufacture of regulations in cooperation with the department of youth and sports and the DPRD Riau province with the approval of the governor .Keywords : Oligarchy = Friend , Family , Alumni